2008
DOI: 10.1029/2008jc004776
|View full text |Cite
|
Sign up to set email alerts
|

Radon and radium isotope assessment of submarine groundwater discharge in the Yellow River delta, China

Abstract: [1] Naturally occurring chemical tracers were used to assess the magnitude of submarine groundwater discharge (SGD) during two different sampling periods at a coastal site south of the Yellow River delta, China. We used salinity and pH as indicators of the terrestrial and recirculated seawater components of discharging groundwater and radium isotopes to quantify offshore transport rates. We then used an hourly time series of multiple radium isotopes ( 224 Ra, 223 Ra, and 226 Ra) to quantify SGD rates and also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
76
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 129 publications
(79 citation statements)
references
References 42 publications
3
76
0
Order By: Relevance
“…In this section, the magnitude of SGD and its importance as source of NO spatial distribution of 222 Rn was typically mapped during one survey (Peterson et al 2008), the 222 Rn distribution was observed through 12 months of synoptic surveys. The sampling strategy was intended to account for the seasonal variation of 222 Rn concentration in the estuary.…”
Section: Discussionmentioning
confidence: 99%
“…In this section, the magnitude of SGD and its importance as source of NO spatial distribution of 222 Rn was typically mapped during one survey (Peterson et al 2008), the 222 Rn distribution was observed through 12 months of synoptic surveys. The sampling strategy was intended to account for the seasonal variation of 222 Rn concentration in the estuary.…”
Section: Discussionmentioning
confidence: 99%
“…In areas where advective groundwater inflow could be verified by significantly higher excess radon concentrations, the influence of diffusive radon input was considered insignificant. The applied approach is common in other environments where advective groundwater discharge dominates other radon inputs (Cable et al, 1996;Peterson et al, 2008).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Following the approach of Peterson et al (2008), Eq. (12) was used to estimate the SGD flux as follows:…”
Section: Sgd Derived From the Tidal Cyclesmentioning
confidence: 99%
“…Similar to that of Ra activity, DIN and DSi variations had an opposite trend to salinity despite a small hysteresis effect observed (Figure 6c). There sources, such as SGD (e.g., Peterson et al, 2008;Moore, 2010 Ra balance as follows (Moore, 2003): 1.00 …”
mentioning
confidence: 99%